Innovative mycoremediation technique for treating unsterilized PCDD/F-contaminated field soil and the exploration of chlorinated metabolites. (15th November 2021) - Kaewlaoyoong, Acharee; Chen, Jenq-Renn; Cheng, Chih-Yu; Lin, Chitsan; Cheruiyot, Nicholas Kiprotich; Sriprom, Pongsert
Abstract: Mycoremediation of unsterilized PCDD/F-contaminated field soil was successfully demonstrated by solid-state fermentation coupled with Pleurotus pulmonarius utilizing a patented incubation approach. The experiments were carried out in four setups with two as controls. The contaminated soil was homogenously mixed with solid inocula, 1:0.5 dry w/w, resulting in an initial concentration of 4432 ± 623 ng WHO-TEQ kg −1 . After a 30-day incubation under controlled conditions, the overall removal (approx. 60%) was non-specific. The removal was attributed to degradation by extracellular ligninolytic enzymes and uptake into the fruiting tissue (~110 ng WHO-TEQ kg −1 of mushroom). Furthermore, less recalcitrant chlorinated metabolites were found, implying ether bond cleavage and dechlorination happened during the mycoremediation. These metabolites resulted from the complex interaction between P. pulmonarius and the indigenous microbes from the unsterilized soil. This study provides a new step toward scaling up this mycoremediation technique to treat unsterilized PCDD/F-contaminated field soil. Graphical abstract: Image 1 Highlights: A patented technique was developed to treat unsterilized PCDD/F-contaminated soil. The overall PCDD/F degradation was non-specific, with 60% removal after 30 days. PCDD/F translocation in Pleurotus pulmonarius ' fruiting body was confirmed. Less recalcitrant metabolites, and enzymatic mediators and biosurfactants occurred. The systematic technique can be easily upscaled for field-scale application.